The exposure to uteroplacental insufficiency is associated with activation of unfolded protein response in postnatal life. - Annalisa Deodati; Josepmaría Argemí; Daniela Germani; Antonella Puglianiello; Anna Alisi; Cristiano De Stefanis; Roberto Ferrero; Valerio Nobili; Tomás Aragón; Stefano Cianfarani (PLoS ONE)
Early life events are associated with the susceptibility to chronic diseases in adult life. Perturbations of endoplasmic reticulum (ER) homeostasis activate the unfolded protein response (UPR), which contributes to the development of metabolic alterations. Our aim was to evaluate liver UPR in an animal model of intrauterine growth restriction (IUGR). A significantly increased expression of X-box binding protein-1 spliced (XBP1s) mRNA (p<0.01), Endoplasmic Reticulum-localized DnaJ homologue (Erdj4) mRNA (p<0.05) and Bip/GRP78-glucose-regulated protein 78 (Bip) mRNA (p<0.05) was observed in the liver of IUGR rats at birth. Furthermore, the expression of gluconeogenesis genes and lipogenesis genes were significantly upregulated (p<0.05) in IUGR pups. At 105 d, IUGR male rats showed significantly reduced glucose tolerance (p<0.01). A significant decreased expression of XBP1s mRNA (p<0.01) and increased expression of double-stranded RNA-dependent protein kinase-like ER kinase (PERK) and Asparagine synthetase (ASNS) (p<0.05) was observed in the liver of IUGR male adult rats. Liver focal steatosis and periportal fibrosis were observed in IUGR rats. These findings show for the first time that fetal exposure to uteroplacental insufficiency is associated with the activation of hepatic UPR and suggest that UPR signaling may play a role in the metabolic risk.